O. H. Hauptmann, Escorial Bible I.j.4. Volume I: The Pentateuch. University of Pennsylvania Press for Grinnell College Press, Philadelphia, 1953; xii + 320 pp. - Raphael Levy (Nueva Revista de Filología Hispánica, 1954)
Se reseñó el libro: Escorial Bible I. j. 4. Volume I: The Pentateuch.